Insights into lithospheric architecture, fertilisation and fluid pathways from AusLAMP MT. Issue 1 (1st December 2016) - Thiel, Stephan; Reid, Anthony; Heinson, Graham; Robertson, Kate
Abstract : The Australian Lithospheric Architecture Magnetotelluric Project (AusLAMP) has the goal to map the electrical resistivity of the Australian lithosphere to constrain the geodynamic framework of the continent. Data acquisition in South Australia has covered two-thirds of the state to date. Three-dimensional resistivity models of subsets of the AusLAMP grid across the Gawler Craton show a generally electrically resistive crust and lithosphere, but an area of low resistivity between depths of 100 km and 200 km beneath the Gawler Range Volcanics exists. A possible explanation is a fertilised mantle signature as a result of metasomatic events in the Proterozoic. The continuous low resistivity connection along the margins of the Gawler Craton core to the surface coincides with the prospective IOCG belt along the eastern margin of the Gawler Craton. The results support the importance of the AusLAMP project to define the lithospheric architecture of the continent and the value of primary lithospheric architecture for mineral exploration.